Data set on effect of amaranth proteins on the RAS system. In vitro, in vivo and ex vivo assays - Suárez, Santiago (2020)
Data set presented in this article is related to the research paper entitled “Effect of amaranth proteins on the RAS system. In vitro, in vivo and ex vivo assays”, available in Food Chemistry [1]. In this article, we evaluated the effect on systolic blood pressure of spontaneously hypertensive rats (SHR) of different samples with amaranth proteins/peptides. The effect of these samples on RAS system was evaluated using in vitro and ex vivo assays. The concentration of renin and angiotensin converting enzyme (ACE) was evaluated using two commercial ELISA kits. Renin concentration was estimated through a direct immunoassay and ACE concentration with an immunoassay based on a competitive inhibition. In addition, the ACE inhibitory activity in plasma was evaluated using a spectrophotometric assay according to [2]. Ex vivo experiments were done with thoracic aorta extracted during the surgical procedure employed to obtain blood samples according to [3]. Data presented in this article recollect a very extensive work on how can be affect the RAS system in SHR model using amaranth protein/peptides as potential antihypertensive samples. These data could be useful to design novel functional foods for hypertensive individuals.